Preliminary ultrasonography study of the pancreas in the dromedary camel (Camelus dromedarius) - Lakhel, El Hassania; El Allali, Khalid; Achaâban, Mohamed Rachid; Azrib, Rahma (Frontiers in Veterinary Science, 2025)
IntroductionPancreatic lesions in camels can lead to significant economic losses. They are practically undetectable, as clinical signs alone are insufficient for specific diagnosis. Ultrasonography is a valuable diagnostic tool for evaluating the pancreas. However, ultrasonographic reference patterns of the pancreas in the camel are yet to be established. This study aimed to define the ultrasonographic appearance, reference values, location, and acoustic window for evaluating the pancreas in healthy camels.MethodsEight adult and 14 young Moroccan camels were investigated by ultrasonography using a micro-convex probe with SIUI CTS-900 V and Samsung MH70A Doppler ultrasound scanners at 3.5 MHz.ResultsThe body of the pancreas was scanned just below the right kidney, behind the 12th rib; an ultrasonographic pattern of pancreatic parenchyma appeared as a hyperechoic elongated band, including the portal vein, with a Doppler flow response. The average thickness of the body was 3.60 ± 0.24 cm (n = 14) in young camels significantly lower than in adult camels 4.61 ± 0.26 cm (n = 8). The right lobe was scanned on the right side, adjacent to the duodenal ampulla and abomasum, beneath the liver along the 11th, 10th, and 9th intercostal spaces. The ultrasonographic pattern of parenchyma appeared as a hyperechoic triangle compared to the liver, including portal and duodenal-pancreatic veins, showing a Doppler flow response. The corresponding parenchyma thickness within the three intercostal spaces was 3.93 ± 0.33 cm, 4.40 ± 0.20 cm, and 3.46 ± 0.39 cm in the young camels (n = 14), and 4.99 ± 0.46 cm, 5.90 ± 0.27 cm, and 4.11 ± 0.68 cm in the adults (n = 8), respectively. The pancreatic major duct was seen as an anechoic circle with a hyperechoic wall, with a maximum diameter of 1 cm, and the left lobe scanned beneath the cranial extremity of the spleen; its ultrasonographic pattern showed an irregular hypoechoic band with a mean thickness of 2.32 ± 0.32 cm (n = 14) in young camels and 3.08 ± 0.52 cm (n = 8) in the adults, including a small splenic vein.ConclusionUltrasonography combined with Doppler techniques provides valuable information on pancreatic health, blood flow, and tissue perfusion, aiding early detection of pancreatic diseases and, consequently, minimizing economic losses in camel husbandry.